Lenvatinib in combination with golvatinib overcomes hepatocyte growth factor pathway‐induced resistance to vascular endothelial growth factor receptor inhibitor. Issue 6 (28th April 2014) - Nakagawa, Takayuki; Matsushima, Tomohiro; Kawano, Satoshi; Nakazawa, Youya; Kato, Yu; Adachi, Yusuke; Abe, Takanori; Semba, Taro; Yokoi, Akira; Matsui, Junji; Tsuruoka, Akihiko; Funahashi, Yasuhiro
<x xml:space="preserve">Abstract</x> Vascular endothelial growth factor receptor (VEGFR) inhibitors are approved for the treatment of several tumor types; however, some tumors show intrinsic resistance to VEGFR inhibitors, and some patients develop acquired resistance to these inhibitors. Therefore, a strategy to overcome VEGFR inhibitor resistance is urgently required. Recent reports suggest that activation of the hepatocyte growth factor (HGF) pathway through its cognate receptor, Met, contributes to VEGFR inhibitor resistance. Here, we explored the effect of the HGF/Met signaling pathway and its inhibitors on resistance to lenvatinib, a VEGFR inhibitor. In in vitro experiments, addition of VEGF plus HGF enhanced cell growth and tube formation of HUVECs when compared with stimulation by either factor alone. Lenvatinib potently inhibited the growth of HUVECs induced by VEGF alone, but cells induced by VEGF plus HGF showed lenvatinib resistance. This HGF‐induced resistance was cancelled when the Met inhibitor, golvatinib, was added with lenvatinib. Conditioned medium from tumor cells producing high amounts of HGF also conferred resistance to inhibition by lenvatinib. In s.c. xenograft models based on various tumor cell lines with high HGF expression, treatment with lenvatinib alone showed weak antitumor effects, but treatment with lenvatinib plus golvatinib showed synergistic antitumor effects, accompanied by decreased tumor vessel density. These results suggest that HGF from tumor cells confers resistance to tumor endothelial cells against VEGFR inhibitors, and that combination therapy using VEGFR inhibitors with Met inhibitors may be effective for overcoming resistance to VEGFR inhibitors. Further evaluation in clinical trials is warranted.